Sustentabilidade financeira das Instituições de Ensino Superior privadas: um modelo de gestão estratégica com base no sistema nacional de avaliação da educação superior (SINAES) - Silva, Renato (2016)
The applied qualitative research has focused on proposing a Strategic Management Model for Private Higher Education Institutions (‘MGE/IES’), in view of the financial sustainability of these Institutions. The research has taken from the assumption that strategic management is one of the central elements for the accomplishment of what the dimensions of the Higher Education Assessment System (‘SINAES’) and the perenniality of private ‘IES’ have been. Therefore, the aforementioned Model has been developed with reference to: a) the evaluative dimensions contained in the Higher Education Evaluation System, and b) the theoretical and methodological assumptions related to strategic management, such as the Strategic Planning, the Balanced Scorecard (BSC), the Business Model Canvas, and the PDCA Cycle. For the construction of the structuring pillars of the ‘MGE/IES’, a review of the literature on that subject has been carried out. Based on this study, the Strategic Management Model for Private Higher Education Institutions has been structured in five stages: Stage 1: National System of Evaluation of Higher Education; Stage 2: Strategic Planning; Step 3: Structuring of the strategic planning in the business blocks of the Business Model Canvas; Stage 4: Categorization of the business blocks of the Business Model Canvas at four perspectives of the Balanced Scorecard (BSC); Stage 5: Monitoring of the indicators and ongoing evaluation of results based on the PDCA. We have expected that the literature review on the research topic can contribute to the advancement of the discussions about strategic management in private ‘IES’, especially regarding to the interrelations between management and the quality of higher education with financial sustainability. In addition, we have expected that the developed model will constitute into a theoretical-methodological reference that can be adopted by the private ‘IES’, contributing to the management of the financial sustainability of these Institutions.